Nucleotide sequence of the structural gene for dUTPase of Escherichia coli K-12. - Lundberg, L G (1983)
The nucleotide sequence of the dUTPase structural gene, dut, of Escherichia coli has been determined. The DNA sequence predicts a polypeptide chain of 150 amino acid residues (mol. wt. 16 006) corresponding in size and composition to the purified dUTPase subunit. In a tentative promoter region preceding the dut gene, the -35 and -10 regions are separated by a SacI (SstI) site. Cloning of the dut gene utilization this SacI site was previously shown to reduce dut expression dramatically. The nucleotide sequence also contains a 210-codon open reading frame 106 bp downstream of dut and co-directional with dut. Previous protein synthesis experiments using dut plasmids allocated the gene of a polypeptide of mol. wt. 23 500 to this DNA region. The open reading frame thus may correspond to a protein of unknown function co-transcribed with the dut gene.